Efektivitas PERDA Kabupaten Padang Lawas Utara No. 3 Tahun 2013 tentang PBB Pedesaan dan Perkotaan dalam Rangka Peningkatan PAD - Burhan (Inovasi Pratama Internasional. Ltd, 2022)
Rural and Urban Land and Building Tax is one type of regional retribution that has great potential and is expected to contribute to regional income. The formulation of the problem in this study is how to regulate Rural and Urban Land and Building Taxes in North Padang Lawas Regency, how to implement North Padang Lawas Regency Regional Regulation Number 3 of 2013 concerning Rural and Urban Land and Building Taxes in the Context of Increasing PAD, What are the Obstacles to Implementing Regulations North Padang Lawas Regency No. 3 of 2013. This study uses a descriptive method through a normative approach to obtain secondary data. The collected data will be analyzed carefully using qualitative analysis or described in sentences. The results of the research on Rural and Urban Land and Building Tax regulations in North Padang Lawas Regency are regulated in North Padang Lawas Regency Regional Regulation Number 3 of 2013 concerning Rural and Urban Land and Building Taxes which are intended to support and encourage economic growth and development in North Padang Lawas Regency. in addition to being a source of Regional Original Income. The implementation has been going quite well, has a simple flow and does not make it difficult for taxpayers, it is intended to increase local revenue in order to increase regional development. Barriers to the implementation of the North Padang Lawas Regency Regulation Number 3 of 2013 concerning Rural and Urban Land and Building Taxes include the economy, taxpayer disorder, inaccuracy of officers, weak law enforcement on tax compliance for state administrators.